(untitled) (Third Sector Social Economic Review, 2026)
This study aims to comparatively examine the sustainability of mortgage loans in Türkiye and Germany within the framework of macroeconomic conditions and financing structures. Using indicators such as housing loans, mortgage interest rates, inflation, housing price indices, and Gross Domestic Product (GDP) for the period 2014–2025, the housing finance markets of the two countries are evaluated using a descriptive and comparative analysis method. Within the analysis, the share of housing loan stock in GDP is considered one of the key indicators reflecting the economic weight and sustainability level of the mortgage market. The findings show that the mortgage system in Germany follows a more balanced course thanks to its institutional structure, long-term financing opportunities, and relatively stable macroeconomic conditions. In contrast, it has been determined that high inflation, fluctuations in interest rates, and increases in funding costs have had limiting effects on housing finance indicators in Türkiye. In particular, the decline in Türkiye ’s housing loan portfolio as a percentage of GDP from approximately 5.3% in 2017 to 0.9% in 2024 reveals a significant decrease in the weight of the mortgage market within the overall economic size. Accordingly, this study emphasizes that a sustainable housing finance system should be evaluated not only in terms of loan volume but also in conjunction with macroeconomic stability, interest rate structure, institutional framework, and funding diversity. It is believed that this study will contribute to the literature by offering a comparative perspective on the sustainability of the mortgage market in Türkiye based on current data.